2000
DOI: 10.1080/713654922
|View full text |Cite
|
Sign up to set email alerts
|

Methods to improve the hatchability of checked chicken eggs

Abstract: 1. The hatchability of checked Leghorn and broiler parent hatching eggs was significantly improved by shell treatment: smearing with synthetic adhesive resin (Fevicol), or pasting cellophane tape or insulation tape over the checked portion of the shell. 2. Shell damage reduced hatchability by increasing evaporative loss, leading to embryonic dehydration. 3. Relative chick weight, expressed as a percentage of egg weight was lower in untreated checked eggs but comparable between intact and shell-treated hatching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
4
8
0
2
Order By: Relevance
“…Nascimento et al (1992) showed that bacterial penetration is not related to eggshell pore numbers, and could be independent from changes in gas and water conductance of the embryo. Our results are generally in agreement with the study of Narahari et al (2000), who reduced EM by covering eggshell cracks with either resin, cellophane or insulation tape.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Nascimento et al (1992) showed that bacterial penetration is not related to eggshell pore numbers, and could be independent from changes in gas and water conductance of the embryo. Our results are generally in agreement with the study of Narahari et al (2000), who reduced EM by covering eggshell cracks with either resin, cellophane or insulation tape.…”
Section: Discussionsupporting
confidence: 92%
“…Traldi et al (2011) explained that CW is highly influenced by egg weight. Our findings are in close agreement with Narahari et al (2000), who applied different eggshell treatments (synthetic adhesive resin, cellophane or insulation tape) to cracked eggs. The CW/EW ratio was similar among the positive control (UE) and NV, CV and MP groups; and the average value (68.49 ± 0.40) was in line with the proportion (67%) proposed by Ross (2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…El peso de los pollos al nacimiento no mostró diferencia entre tratamiento, esto pudo ser a que ambos tratamientos provenían de la misma edad de reproductora; aunque guarda una relación directa con el peso del huevo y peso del saco vitelino (Barbosa, et al, 2012;Suárez et al;, Wilson, 1991Narahara et al, 2000). La edad de la reproductora afecta la incubabilidad, por lo que se tiene una relación lineal positiva conforme aumenta la edad de la reproductora y hay un aumento del tamaño del huevo, peso del pollo; más sin embargo hay una correlación lineal negativa entre la edad de la reproductora y la incubabilidad.…”
Section: Discussionunclassified